Prevalência de oftalmopatias em cães naturalmente infectados com Leishmania (Leishmania) Chagasi no município de Belo Horizonte - Estudo clínico e Histopatológico. - Gustavo de Oliveira Fulgencio (2006)
Visceral canine leishmaniasis is among the parasitic disease with important ocular manifestations. They can vary from small alterations in the ophthalmic enclosures until complete visual loss. The dogs with ocular leishmaniasis must commonly present for a variety of systemic signs. However, in some dogs, abnormalities involving the eyes were the presenting complaint by the owners. The prevalence of ocular lesions in dogs with systemic leishmaniasis has been reported to vary between 24,1% and 80,5%. The purpose of this study was to determine the prevalence of ocular lesions associated with leishmaniasis in dogs in Belo Horizonte city, Brazil. One hundred of canine leishmaniasis with many breeds confirmed cytological, serologically or both were used. The ophthalmic lesions were present in 48 dogs (96 eyes) and the most common manifestation were blepharitis (23,9%), anterior uveitis (20,8%), conjunctivitis (19,8%), keratoconjuntivitis sicca (18,7%), periocular alopecia (12,5%), panuveitis (7,3%) retinal detachment (7,3%) and keratitis (6,2%). Cataract, nuclear sclerosis and nodule iris and eyelid were diagnosed, although no probable relationship can be established. Ophthalmic manifestations are among the most peculiar clinical lesions of canine leishmaniasis and this zoonotic disease should be include in the differential diagnosis in animals coming from endemic areas.